Putative Bifunctional Chorismate Mutase/Prephenate Dehydratase Contributes to the Virulence of Acidovorax citrulli - Kim, Minyoung; Lee, Jongchan; Heo, Lynn; Han, Sang-Wook (Frontiers in Plant Science, 2020)
Acidovorax citrulli (Ac) is a plant pathogenic bacterium that causes bacterial fruit blotch (BFB) in cucurbit crops. Despite its importance in the cucurbit industry, resistant cultivars/lines against BFB have not yet been identified. Therefore, there is a need to characterize the virulence factors/mechanisms in Ac to control the disease. Chorismate mutase, a key enzyme in the shikimate pathway, produces aromatic amino acids. Here, we report the functions of putative bifunctional chorismate mutase/prephenate dehydratase in Ac (CmpAc) determined by proteomic analysis and phenotypic assays. Ac strain lacking CmpAc, AcΔcmpAc(EV), were significantly less virulent on watermelon in the germinated-seed inoculation and leaf infiltration assays. Sequence analysis revealed that CmpAc possesses two distinct domains: chorismate mutase and prephenate dehydratase, indicating that CmpAc is a bifunctional protein. Auxotrophic assays demonstrated that CmpAc is required for the biosynthesis of phenylalanine, but not tyrosine. The comparative proteomic analysis revealed that CmpAc is mostly involved in cell wall/membrane/envelop biogenesis. Furthermore, AcΔcmpAc(EV) showed reduced twitching halo production and enhanced biofilm formation. In addition, AcΔcmpAc(EV) was less tolerant to osmotic stress but more tolerant to antibiotics (polymyxin B). Thus, our study provides new insights into the functions of a putative bifunctional protein related to virulence in Ac.